Phytochemical Characterization and Insecticidal Property of Jatropha Plant (Global Journal of Science Frontier Research, 2016)
Phytochemical analysis on the pulverized leaf sample of Jatropha curcas as well as the insecticidal activity of the ethanolic leaf extract on Callosobruchus maculatus was carried out. The study investigated the mortality rate as a result of treatment of grains with the leaf extract at different dilutions of 20, 40, 60, 80 and 100mg/ml. These were tested against C. maculatus by treating 20g of bean sample with the extract and then infesting each in a plastic container with 20 adults of the insect and the untreated grains were used as the control. The plant extract resulted in a significant increase (P
Keywords: jatropha curcas; extract; callosobruchus maculatus; phytochemicals